Internalisasi Ajaran Catur Guru dalam Membentuk Karakter Siswa di SDN 2 Sesetan - Chandewi, Ni Kadek Deny (Samsara Institute Publisher, 2025)
This research aims to analyze how the internalization of the teachings of Catur Guru shapes the character of students at SDN 2 Sesetan. The teachings of Catur Guru, which consist of Guru Rupaka, Guru Pengajian, Guru Wisesa, and Guru Swadhyaya, are implemented in various school activities to instill moral and spiritual values in students. This study uses a qualitative approach with a case study method, involving direct observations, interviews, and documentation to obtain data related to the implementation of Catur Guru teachings. The results of the study show that the internalization of the Catur Guru teachings plays a significant role in shaping the character of students at SDN 2 Sesetan. Through routine activities such as prayers, religious ceremonies, and interactions with teachers and parents, students are taught to respect their teachers, parents, and others. The application of Asta Brata in the school context also strengthens students' character, particularly in discipline, leadership, and social responsibility. The study concludes that collaboration between the school, family, and community in internalizing these teachings is essential to create students with noble character who are ready to contribute positively to society.